226k views
2 votes
Which expression is equal to (2x−2)(3x−3)?

User Sth
by
5.6k points

2 Answers

3 votes

(2x−2)(3x−3)

=6x^2 -6x -6x +6

=6x^2 - 12x + 6

User Vitor Tyburski
by
6.1k points
4 votes

Answer:

(6x²- 12x + 6)

Explanation:

The given expression is (2x - 2)(3x - 3).

Since (2x - 2) = 2(x - 1)

and (3x - 3) = 3(x - 1)

Now (2x - 2)(3x - 3) = [2(x - 1)][3(x - 1)]

= (2×3)(x - 1)(x - 1)

= 6(x - 1)²

= 6(x² - 2x + 1)

= (6x² - 12x + 6)

Therefore, the given expression is equal to (6x² - 12x + 6).

User Nowhere
by
5.8k points